In silico analysis of Sulpiride, synthesis, characterization and in vitro studies of its nanoparticle for the treatment of schizophrenia - Keçel Gündüz, S.; Budama Kilinç, Y.; Çakır Koç, R.; Zorlu, T.; Bıçak, B.; Kökçü, Y.; Kaya, Z.; Özel, A.E.; AKYÜZ, SEVİM (My University, 2019)
Background: Sulpiride,which has selectively dopaminergic blocking activity, is a substituted benzamide antipsychotic drug plays a prominent role in the treatment of schizophrenia, more selective and primarily blocks dopamine D2 and D3 receptor. Objective: This study has two main objectives, firstly; the molecular modeling studies (MD and Docking, ADME) were conducted to define the molecular profile of sulpiride and sulpiride-receptor interactions. The another aim of this study was to synthesize polymeric nanoparticles with chitosan, having the advantage of slow/controlled drug release, to improve drug solubility and stability, enhances utility, and reduces toxicity. Method: Molecular dynamic simulation was applied to determine the conformational change and stability (in water) of the drug and the binding profile to D3 dopamine receptor was performed by molecular docking calculations. The pharmacological properties of the drug were revealed by ADME analysis. The ionic gelation method was used to prepare sulpiride loaded chitosan nanoparticles (CS NPs). The Dynamic Light Scattering (DLS), UV–vis absorption (UV), Scanning Electron Microscopy (SEM), Fourier transform infrared (FT-IR) spectroscopy techniques were carried out to characterize the nanoparticles. In vitro cell cytotoxicity experiments examined with MTT assay on mouse fibroblast (L929), human neuroblastoma (SH-SY5Y) and glioblastoma cells (U-87). The statistical evaluations were produced by ANOVA. Results: The residues (ASP-119, PHE-417) of D3 receptor provided a stable docking with the drug, and the important pharmacological values (blood brain barrier, cacao2 permeability and human oral absorption) were also determined.The average particle size, PdI and zeta potential value of sulpiride-loaded chitosan NPs having a spherical morphology were calculated as 96.93 nm, 0.202, and +7.91 mV. The NPs with 92.8% encapsulation and 28% loading efficiency were found as an slow release profile with 38.49% at the end of the 10th day. Due to the formation of encapsulation, the prominent shifted wavenumbers were also identified. Mitochondrial activity of U87, SHSY-5Y and L929 cell line were assayed and evaluated using the SPSS program. Conclusion: To provide more efficient use of Sulpiride having a low bioavailability of the gastrointestinal tract, the nanoparticle formulation with high solubility and bioavailability was designed and synthesized for the first time in this study for the treatment of schizophrenia. In addition to all pharmacological properties of drug, the dopamine blocking activity was also revealed. The toxic effect on different cell lines have also been interpreted.
Keywords: MD; ADME; Controlled Release System; Docking